Prolonged oral coenzyme Q10-β-cyclodextrin supplementation increases skeletal muscle complex I+III activity in young Thoroughbreds - M.F. Rooney; C.E. Curley; J. Sweeney; M.E. Griffin; R.K. Porter; E.W. Hill; L.M. Katz (Journal of Applied Animal Nutrition)
Coenzyme Q10 (CoQ10) is an essential component of the mitochondrial electron transport chain (ETC). Decreased skeletal muscle CoQ10 content may result in decreased ETC activity and energy production. This study tested the hypotheses that supplementation with oral CoQ10 will increase plasma CoQ10 concentrations and that prolonged supplementation will increase skeletal muscle CoQ10 content in young, healthy untrained Thoroughbreds. Nineteen Thoroughbreds (27.5±9.7 months old; 11 males, eight females) from one farm and maintained on a grass pasture with one grain meal per day were supplemented daily with 1.5 mg/kg body weight of an oral CoQ10-β-cyclodextrin inclusion complex. Whole-blood and skeletal muscle biopsies were collected before (T0) and after (T1) nine weeks of supplementation. Plasma CoQ10 concentrations were determined via high-performance liquid chromatography. Skeletal muscle mitochondrial ETC combined complex I+III enzyme activity (indirect measurement of CoQ10 content) was assessed spectrophotometrically and normalised to mitochondrial abundance. Horses accepted supplementation with no adverse effects. Plasma CoQ10 concentration increased in all horses following supplementation, with mean plasma CoQ10 concentration significantly increasing from T0 to T1 (0.13±0.02 vs 0.25±0.03 μg/ml; mean difference 0.12±0.03; P=0.004). However, variability in absorbance resulted in a 58% response rate (i.e. doubling of T1 above T0 values). The mean skeletal muscle complex I+III activity significantly increased from T0 to T1 (0.36±0.04 vs 0.59±0.05 pmol/min/mg of muscle, mean difference 0.23±0.05; P=0.0004), although T1 values for three out of 19 horses decreased on average by 23% below T0 values. In conclusion, oral supplementation with CoQ10 in the diet of young, healthy untrained Thoroughbreds increased mean plasma CoQ10 concentration by 99% with prolonged daily supplementation increasing mean skeletal muscle complex I+III activity by 65%. Additional research is warranted investigating training and exercise effects on skeletal muscle CoQ10 content in CoQ10 supplemented and un-supplemented Thoroughbreds.